Study on Growth and Yield Performance of High Yielding Rice (Oryza sativa L.) Varieties under Rainfed Lowland Condition of Nagaland - Jamir, T.; Gohain, T. (International Journal of Bio-resource and Stress Management, 2017)
Crop genotype plays a dominant role in crop production systems. They affect crop productivity by their higher yield potentials, resistance against insect pest and diseases under different climatic conditions. To evaluate different varieties of rice for their growth and yield characteristics, an experiment was conducted to investigate high yielding rice (Oryza sativa L.) varieties under rainfed lowland condition of Nagaland at Neiphrelie Colony, Chumukedima during the kharif season of 2016. The study treatments adopted were eleven rice varietiies viz., Ranjit, Bahadur, Aghonibora, Satyaranjan, Moniram, Kushal, Mulagabharu, Bokuljoha, Basundara, Piolee and Ketikijoha (HYV rice released by AAU) at a spacing of 20×15 cm2 using 3-4 seedling hill-1. The experiment was set in Randomized block design (RBD) with three replications. Almost all the varieties were found to be semi-dwarf in nature. Data on various growth and yield parameters revealed that Satyaranjan produced higher number of tillers hill-1 (23.44), no. of panicle hill-1 (22), yield (59.96 q ha-1) and harvest index (43.70). The length of panicle was found highest in Moniram (26.45 cm) and lowest in Basundara (21.51 cm). Bokuljoha recorded highest straw yield (94.38 q ha-1) and lowest filled grain percentage (73.17) and test weight (10.87 g). Filled grain percentage was found highest in Ranjit (86.72) and the highest test weight was recorded in Aghonibora (26.01 g). The rice varieties Satyaranjan (59.96 q ha-1), Ranjit (57.01 q ha-1) and Kushal (56.39 q ha-1) can be successfully cultivated under rainfed lowland condition of Nagaland.